Takikardia Supraventrikular Paroksismal pada Pemberian Ondansentron Intravena: Suatu Laporan Kasus - Erick Hoetama (The Indonesian Heart Association, 2015)
Ondasentron is selective serotonin 5-HT3 receptor antagonist. It is widely used as the drug of choice for preventing nausea and vomiting associated with chemotheraphy and post-surgery. This drug become more popular because it’s superior efficacy and minimal side effect. Although cardiovascular adverse effect caused by ondansentron administration is rare, some cardiovascular events have been reported, from atrial fibrillation to fatal ventricular tachycardia. This case reports paroxysmal supraventricular tachycardia in male 23 years old following administration of 4 mg intravenous ondansentron